Cross-cultural adaption and inter-rater reliability of the Swedish version of the updated clinical frailty scale 2.0 - Henrik Olsson; Kristina Åhlund; Joakim Alfredsson; David Andersson; Anne-Marie Boström; Susanne Guidetti; Mattias Prytz; Niklas Ekerstad (BMC Geriatrics, 2023)
Abstract Background Worldwide, there is a large and growing group of older adults. Frailty is known as an important discriminatory factor for poor outcomes. The Clinical Frailty Scale (CFS) has become a frequently used frailty instrument in different clinical settings and health care sectors, and it has shown good predictive validity. The aims of this study were to describe and validate the translation and cultural adaptation of the CFS into Swedish (CFS-SWE), and to test the inter-rater reliability (IRR) for registered nurses using the CFS-SWE. Methods An observational study design was employed. The ISPOR principles were used for the translation, linguistic validation and cultural adaptation of the scale. To test the IRR, 12 participants were asked to rate 10 clinical case vignettes using the CFS-SWE. The IRR was assessed using intraclass correlation and Krippendorff’s alpha agreement coefficient test. Results The Clinical Frailty Scale was translated and culturally adapted into Swedish and is presented in its final form. The IRR for all raters, measured by an intraclass correlation test, resulted in an absolute agreement value among the raters of 0.969 (95% CI: 0.929–0.991) and a consistency value of 0.979 (95% CI: 0.953–0.994), which indicates excellent reliability. Krippendorff’s alpha agreement coefficient for all raters was 0.969 (95% CI: 0.917–0.988), indicating near-perfect agreement. The sensitivity of the reliability was examined by separately testing the IRR of the group of specialised registered nurses and non-specialised registered nurses respectively, with consistent and similar results. Conclusion The Clinical Frailty Scale was translated, linguistically validated and culturally adapted into Swedish following a well-established standard technique. The IRR was excellent, judged by two established, separately used, reliability tests. The reliability test results did not differ between non-specialised and specialised registered nurses. However, the use of case vignettes might reduce the generalisability of the reliability findings to real-life settings. The CFS has the potential to be a common reference tool, especially when older adults are treated and rehabilitated in different care sectors.